Can fossil bones and teeth be dated using fission track analysis? - Jolivet, M.; Lebatard, A.-E.; Reyss, J.-L.; Bourlès, D.; Mackaye, H.T.; Lihoreau, F.; Vignaud, P.; Brunet, M. (Chemical geology, 2008)
The high proportion of crystallized apatite forming the bones and teeth should theoretically allow the use of fission track analysis to date vertebrate fossils when burying of the fossiliferous series did not subject them to temperatures exceeding 60 °C. However several major obstacles arise such as the complexity of fossils' internal structures, diagenetic modifications and substitutions of the hydroxyapatite by other minerals, and massive U uptake or loss during diagenesis. In this work, those various problems are addressed combining optical microscope observation of the fossils, a systematic fission track analysis of the best samples, α and γ spectrometry and Secondary Ion Mass Spectrometry. Even if the problems caused by internal structures and mineral substitutions can be solved, U movements in and out of the fossils are generally too complex to allow fission track analysis dating of the fossils.